Improving Environmental Sanitation Knowledge through Clean and Healthy Living Behavior (CHLB) Education - Saftia Aryzki; Noverda Ayuchecaria; Ana Khumaira Sari (Universitas Lambung Mangkurat, 2024)
Environmental cleanliness is always associated with health because maintaining a clean environment can prevent the emergence of various types of diseases. This service activity aims to increase awareness, experiences, and knowledge and foster a sense of community towards a clean and healthy environment to avoid various diseases. This community service method uses service learning (SL), which refers to experiential learning, namely providing direct knowledge to the community regarding the importance of maintaining a clean environment. The activity begins with a pretest, providing CHLB knowledge material on environmental cleanliness, questions and answers, and a post-test. Community service is also accompanied by health checks and the provision of vitamin C supplements and Fe tablets (blood supplements). The results of community service showed that the average pretest and post-test scores for community knowledge in PHBS were 70 and 92.5, the results showed that there was an increase in community knowledge to improve environmental sanitation after being given education regarding CHLB.